IMPACT OF HEALTH EDUCATION PROGRAM ON KNOWLEDGE ABOUT AIDS AND HIV TRANSMISSION IN STUDENTS OF SECONDARY SCHOOLS IN BURAIDAH CITY, SAUDI ARABIA: AN EXPLORATORY STUDY - Saleh, Mahmoud A. (Medknow Publications & Media Pvt Ltd, 1999)
BACKGROUND: Accurate information about Acquired Immunodeficiency Syndrome (AIDS) and Human Immunodeficiency Virus (HIV) is important for their prevention. OBJECTIVES: This study is intended to assess knowledge on AIDS in students of secondary schools in Buraidah city and to measure the effect of a health education program on their knowledge about AIDS in general, modes of HIV transmission and the degree of their misperception about the transmission of the disease through casual contact. METHODOLOGY: A well-designed health education program using personal communication and visual media techniques was conducted for 483 secondary school students in Buraidah secondary schools during the year 1997. Pre and post-tests were done to examine their knowledge about AIDS. RESULTS AND RECOMMENDATIONS: The results of this study pointed out that a health education program on AIDS for students of secondary schools greatly and significantly improved their scores on general knowledge on AIDS views on its transmission and misperception of AIDS (p<0.01). Continuous in-service programs for secondary students are recommended.